Pendampingan Literasi Gizi dan Kepatuhan Minum Obat Pasien TB Anak pada Agrocommunity - Ningtyias, Farida Wahyu; Nafikadini, Iken; Prasetyowati, Irma (UPT Penerbitan Universitas Jember, 2023)
Background: Tuberculosis (TB) is the 10th most deadly disease globally. Indonesia has the third-largest TB incidence in the world. TB in children is often overlooked due to difficult diagnosis and medication adherence. The role of parents with good knowledge is very important to support the prevention and treatment of TB in children. Method: Knowledge improvement was achieved through literacy about nutrition and TB using Flipchart and Flashcard media